Determinants of Perceived Benefits and Ease of Use of the JKN Mobile App Among Outpatients: A Cross-Sectional Study - Ari Sukma Nela; Armen Patria; Prayetni Prayetni (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: The digitization of healthcare services has encouraged the utilization of information technology to improve efficiency, accessibility, and quality of healthcare services. One innovation developed by BPJS Kesehatan is the Mobile JKN application, which facilitates participants in accessing various administrative and healthcare services digitally. However, the utilization of the Mobile JKN application among outpatients remains suboptimal. This condition is assumed to be influenced by users’ perceptions of perceived usefulness and perceived ease of use. Therefore, this study aimed to analyze the determinants of perceived usefulness and perceived ease of use toward the utilization of the Mobile JKN application among outpatients at Bandar Negara Husada Regional General Hospital. Method: This study employed a quantitative approach with a cross-sectional analytical design. The sample consisted of 150 outpatient participants enrolled in the JKN program who were selected based on inclusion and exclusion criteria. Data were collected using a structured questionnaire that assessed respondent characteristics, perceived usefulness, perceived ease of use, and utilization of the Mobile JKN application. Data analysis was conducted using univariate analysis, bivariate analysis with the chi-square test, and multivariate logistic regression analysis. Result: The bivariate analysis demonstrated that perceived usefulness (p = 0.001) and perceived ease of use (p = 0.002) were significantly associated with the utilization of the Mobile JKN application. Furthermore, the multivariate logistic regression analysis revealed that perceived usefulness was the dominant factor influencing Mobile JKN utilization (AOR = 3.26; 95% CI: 1.63–6.51; p = 0.001), while perceived ease of use also showed a significant association (AOR = 2.59; 95% CI: 1.38–4.86; p = 0.003). Conclusion: Perceived usefulness and perceived ease of use significantly influence the utilization of the Mobile JKN application among outpatients. Perceived usefulness was identified as the most dominant factor affecting application utilization. Therefore, efforts to improve users’ understanding of the benefits and ease of use of the Mobile JKN application are necessary to increase the adoption of digital healthcare services among JKN participants.